Biased Perceptions of Income Inequality and Redistribution - Carina Engelhardt; Andreas Wagener (Center for Economic Studies and ifo Institute (CESifo), 2014)
When based on perceived rather than on objective income distributions, the Meltzer-Richards hypothesis and the POUM hypothesis work quite well empirically: there exists a positive link between perceived inequality or perceived upward mobility and the extent of redistribution in democratic regimes - though such a link does not exist when objective measures of inequality and social mobility are used. These observations highlight that political preferences and choices might depend more on perceptions than on factual data.
Keywords: H53; D72; D31; 330; biased perception; majority voting; redistribution